Algunas reflexiones en torno a la enseñanza del análisis económico del derecho en las Universidades Públicas Mexicanas - Ramírez Villaescusa, Rafael (2015)
Economic Analysis of Law is considered by American legal scholars as the principal legal development of the second half of the XX century. Nevertheless, its reception among continental colleagues has been modest. Mexico is not an exception. Our paper explain in a brief and concise manner, what do we understand by economic analysis of law. We therefore, identify some obstacles for its reception inside Mexican public law schools legal academy. Finally we expose some of its possibilities over the national legal context.